Prenatal Low-Protein and Low-Calorie Diets Differentially Alter Arcuate Nucleus Morphology in Newborn Male Rats - Blanco, Noemí; Fernández-García, Jose Manuel; Carrillo, Beatriz; Ballesta, Antonio; García-Úbeda, Rocío; Collado, Paloma; Pinos, Helena (Frontiers in Neuroanatomy, 2022)
Background: Malnutrition during the early stages of development produces alterations that can compromise the functioning of the hypothalamic circuits that regulate food intake. The purpose of the present study is to analyze the effects that a low-protein and low-calorie diet has on the morphology of the arcuate nucleus of the hypothalamus in newborn male and female rats. Methods: On gestational day 6 (G6), 6 pregnant rats were divided into two groups. 3 pregnant rats were fed ad libitum with a control diet (20% casein) and 3 pregnant rats were fed ad libitum with a low-protein (8% casein) and 30% caloric restricted diet. The day of birth, pups were sacrificed resulting in 4 experimental groups: control male, control female, low-protein and low- calorie diet male and low-protein and low-calorie diet female (n=5 in each group). The volume and number of neurons, as well as the neuronal density and number of apoptotic cells were measured. Results: Males on a low-protein and low-calorie diet showed a significant increase in the number of neurons and in the neuronal density of the arcuate nucleus with regard to the rest of the groups studied. These increases were also reflected in the posterior part of the nucleus. Although the existence of sexual dimorphism was not detected in any of the parameters studied in the control groups, the number of neurons and neuronal density showed differences between males and females which were fed with a low-protein and low-calorie diet due to the increase in the number of neurons showed by the male. No significant differences were found in the number of apoptotic cells. Conclusion: Our results show that a low-protein and low-calorie diet during the prenatal stage produces alterations in the arcuate nucleus of the hypothalamus in newborn animals and, more importantly, that the effects of malnutrition are evident in males but not in females. Therefore, it is essential to follow a balanced diet during the early stages of life to ensure optimal development of the neural circuits that regulate eating.